STUDI COMPUTATIONAL FLUID DYNAMICS (CFD) UNTUK MENDIAGNOSA KEGAGALAN POMPA INJEKSI AIR - Machfud, Adam Aliyya; Cahyapala, Reka Adiyasa; Nurrahman, Ardhi Febrian (Jurnal Rekayasa Mesin, 2025)
Multistage centrifugal pumps are the critical equipment in the water injection system in oil and gas processing facilities but often fail due to abrasive and corrosive fluids. This research utilized the Computational Fluid Dynamics (CFD) approach to analyze the effect of sand particle size, produced water characteristics, and cavitation on the performance of three-stages API 610 BB3 water injection pumps. CFD simulations were performed by varying the sand particle size (10 μm, 100 μm, 100 μm) and produced water characteristics from three locations. The standard k-ε turbulence model and the Eulerian granular flow approach were utilized to model the multiphase flow. The results showed a decrease in pump efficiency of up to 10.39% dan head of up to 19.08% in 1000 μm particles. Analysis of the corrosion rate based on water characteristics showed the highest value of 0.198 mm/year at the location with the highest chloride content and conductivity. Cavitation zones were identified around the leading edge of the impeller at each stage. This study provides an in-depth understanding of the failure mechanisms of the water injection pumps. It can form the basis for developing effective mitigation strategies, such as design improvement, material selection and overhaul program.